THE STRUGGLE OF A MOTHER FOR SOCIAL JUSTICE TO AGAINST PATRIARCHAL SYSTEM REFLECTED IN CHANGELING THE MOVIE - AJENG SAPUTRI, RISA RINDU (Jurnal Ilmiah Mahasiswa FIB, 2013)
Women are created equal with men. That is why they need to be treated well in social life. Every people should not differentiate women and men because they have same rights. Their rights are rights which inherent in human nature and existence. Nevertheless domination of patriarchy still emerges in social life. Men still consider women as the weak creatures. Many men still underestimate everything done by women. They think that women cannot do the works which are usually done by men and women are forced to obey everything they said. Therefore, the purpose of this study is to determine how the depiction of social injustice toward women by LAPD in performing their authority in wrong way and how the struggle of a woman in her fight for her rights to get her missing son. And it is also to describe the message of Changeling the movie to the audience. Focus of this research study uses a feminist analysis of Charlotte Perkins Gilman, a Radical Feminist figure, which discusses gender inequality presented in Changeling as research material. The writer uses gender inequality developed by Gilman. Gilman thinks that women and men have different sex principles and women are seen more weak than men by their culture. The results indicate a violation of women’s right by the policemen, that is Christine which is forced by police to admit a child who is not her son. And the police also put her in a psychopathic ward for refusing police orders. But the character of Christine in the film depicts a strong woman who will not give up though oppressed by men because she does it for his son.   Keywordws : Women's Struggle, Social Justice, Patriarchy System, Radical Feminist, Chngeling Movie.